5′-AMP-activated protein kinase is inactivated by adrenergic signalling in adult cardiac myocytes. Issue 2 (21st November 2011) - Tsuchiya, Yugo; Denison, Fiona C.; Heath, Richard B.; Carling, David; Saggerson, David
Abstract : In adult rat cardiac myocytes adrenaline decreased AMPK (AMP-activated protein kinase) activity with a half-time of approximately 4 min, decreased phosphorylation of AMPK (α-Thr 172 ) and decreased phosphorylation of ACC (acetyl-CoA carboxylase). Inactivation of AMPK by adrenaline was through both α1 - and β-ARs (adrenergic receptors), but did not involve cAMP or calcium signalling, was not blocked by the PKC (protein kinase C) inhibitor BIM I (bisindoylmaleimide I), by the ERK (extracellular-signal-regulated kinase) cascade inhibitor U0126 or by PTX (pertussis toxin). Adrenaline caused no measurable change in LKB1 activity. Adrenaline decreased AMPK activity through a process that was distinct from AMPK inactivation in response to insulin or PMA. Neither adrenaline nor PMA altered the myocyte AMP:ATP ratio although the adrenaline effect was attenuated by oligomycin and by AICAR (5-amino-4-imidazolecarboxamide-1-β-D -ribofuranoside), agents that mimic 'metabolic stress'. Inactivation of AMPK by adrenaline was abolished by 1 μM okadaic acid suggesting that activation of PP2A (phosphoprotein phosphatase 2A) might mediate the adrenaline effect. However, no change in PP2A activity was detected in myocyte extracts. Adrenaline increased phosphorylation of the AMPK β-subunit in vitro but there was no detectable change in vivo in phosphorylation of previously identified AMPK sites (β-Ser 24, β-Ser 108 or β-Ser 182 ) suggesting that another site(s) is targeted.